INVESTIGATION OF THE MOTIVATION OF THE SUPPORTERS IN VOLLEYBALL MATCHES IN THE EXAMPLE OF DEAC - Bács, Zalán Mihály; Lente, Lajos (Stadium - Hungarian Journal of Sport Sciences, 2022)
In the present study, we investigated the motivation of people attending volleyball matches of the Debreceni Egyetemi Atlétikai Club. In our complex research, we investigate the passive sports consumption of teams competing in the spectator sports of the DEAC university club. The present study explicitly examines the spectatorship of volleyball, as we are curious to discover whether the followers of different sports show different motivations. The method chosen for the research was a questionnaire delivered online to the target audience using the snowball method. The resulting sample of 128 respondents was relevant to the opinions of 54 respondents. Based on our previous research, we hypothesized that one of the main motivation factors would be the game's beauty and the sport's aesthetics. Our hypothesis was confirmed; our study found that not only one of the main factors but the most important motivating factor is the beauty of the sport; as in the present study, the aesthetics and excitement of volleyball was the most important motivating factor for the respondents.